National spatial data infrastructure (NSDI) of Ukraine: what are its actual, feasible and simultaneously “correct” models? - V. Chabaniuk; O. Dyshlyk (Zemleustrìj, Kadastr ì Monìtorìng Zemelʹ, 2021)
Resume. The actual, feasible and simultaneously "correct" models of digital NSDI of Ukraine are considered in the work. A model of the existed digital NSDI system of Ukraine is named “actual”. This model already differs from the model defined by the [1]. As the latter is unlikely to be implemented in the near future, the issue of the digital feasible NSDI model of Ukraine in the next five years, which would take into account the actual model, is especially acute. In addition to feasibility, such a model must also be "correct", what is proposed in the article. The correct is called a model, the truth of which can be established by inductive or deductive reasoning. To do this, the correct model must be formalized enough so that everyone can verify the authors’ reasoning independently.